Safety and efficacy of abatacept in early diffuse cutaneous systemic sclerosis (ASSET): open-label extension of a phase 2, double-blind randomised trial. (December 2020) - Chung, Lorinda; Spino, Cathie; McLain, Richard; Johnson, Sindhu R; Denton, Christopher P; Molitor, Jerry A; Steen, Virginia D; Lafyatis, Robert; Simms, Robert W; Kafaja, Suzanne; Frech, Tracy M; Hsu, Vivien; et al.
Summary: Background: Abatacept was well tolerated by patients with early diffuse cutaneous systemic sclerosis in a phase 2, double-blind randomised trial, with potential efficacy at 12 months. We report here the results of an open-label extension for 6 months. Methods: Patients (aged ≥18 years) with diffuse cutaneous systemic sclerosis of less than 3 years' duration from their first non-Raynaud's symptom were enrolled into the ASSET trial (A Study of Subcutaneous Abatacept to Treat Diffuse Cutaneous Systemic Sclerosis), which is a double-blind trial at 22 sites in Canada, the UK, and the USA. After completion of 12 months of treatment with either abatacept or placebo, patients received a further 6 months of abatacept (125 mg subcutaneous every week) in an open-label extension. The primary endpoint of the double-blind trial was modified Rodnan Skin Score (mRSS) at 12 months, which was reassessed at 18 months in the open-label extension. The primary analysis included all participants who completed the double-blind trial and received at least one dose of open-label treatment (modified intention to treat). This trial is registered with ClinicalTrials.gov, NCT02161406 . Findings: Between Sept 22, 2014, and March 15, 2017, 88 participants were randomly allocated in the double-blind trial either abatacept (n=44) or placebo (44); 32 patients from each treatment group completed the 6-month open-label extension. Among patients assigned abatacept, a mean improvement from baseline in mRSS was noted at 12 months (−6·6 [SD 6·4]), with further improvement seen during the open-label extension period (−9·8 [8·1] at month 18). Participants assigned placebo had a mean improvement from baseline in mRSS at 12 months (−3·7 [SD 7·6]), with a further improvement at month 18 (−6·3 [9·3]). Infections during the open-label extension phase occurred in nine patients in the placebo–abatacept group (12 adverse events, one serious adverse event) and in 11 patients in the abatacept–abatacept group (14 adverse events, one serious adverse event). Two deaths occurred during the 12-month double-blind period in the abatacept group, which were related to scleroderma renal crisis; no deaths were recorded during the open-label extension. Interpretation: During the 6-month open-label extension, no new safety signals for abatacept were identified in the treatment of diffuse cutaneous systemic sclerosis. Clinically meaningful improvements in mRSS and other outcome measures were observed in both the abatacept and placebo groups when patients transitioned to open-label treatment. These data support further studies of abatacept in diffuse cutaneous systemic sclerosis. Funding: Bristol-Myers Squibb and National Institutes of Health.